2013
DOI: 10.1080/01635581.2013.830314
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidins from Evening Primrose (Oenothera paradoxa) Defatted Seeds Inhibit Invasiveness of Breast Cancer Cells and Modulate the Expression of Selected Genes Involved in Angiogenesis, Metastasis, and Apoptosis

Abstract: There is a growing interest in plant polyphenols (including flavanols) that exhibit pleiotropic biological activities such as antiinflammatory, antioxidant, and anticancer effects. Here, we report for the first time the inhibition of MDA-MB-231 breast cancer cell viability and invasiveness by an evening primrose flavanol preparation (EPFP). We observed a decrease in MDA-MB-231 viability of 50% vs. a control after 72 h of incubation with EPFP at a concentration of 58 μM gallic acid equivalents (GAE) and an inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 47 publications
(63 reference statements)
3
26
0
Order By: Relevance
“…The major proanthocyanidin in evening primrose extract are in dimer and trimer form. 23) This additional evidences confirm that proanthocyanidin in PRFR are the oligomers which might have a similar structure to the proanthocyanidin in the grape seed extract.…”
Section: Discussionsupporting
confidence: 68%
“…The major proanthocyanidin in evening primrose extract are in dimer and trimer form. 23) This additional evidences confirm that proanthocyanidin in PRFR are the oligomers which might have a similar structure to the proanthocyanidin in the grape seed extract.…”
Section: Discussionsupporting
confidence: 68%
“…For instance, Li et al [2010] testing a polyphenol extract from Devil's Club (Oplopanax horridus) on different colorectal cancer cell lines observed that this preparation did not infl uence HT-29 proliferation at all whereas signifi cantly reduced the growth of HCT-116 cell line. Moreover, in our studies, we observed a strong inhibition of MDA-MB-231 human breast cancer cell division by the polyphenol extract from evening primrose [Lewandowska et al, 2013].…”
Section: Discussionmentioning
confidence: 64%
“…After extraction of oil the remaining defatted seeds contain polyphenolic compounds that can have benefi cial health effect. So far, the extracts obtained from defatted seeds from Oenothera paradoxa Hudziok caused a decrease of plasma cholesterol and low density lipoprotein cholesterol in rats [Bałasińska, 1998], a dose-dependent inhibition of lipid peroxidation in mouse lymphocytic leukemic L1210 cells [Bałasińska & Troszyńska, 1998] a dose-dependent inhibition of metallopeptidases activity [Kiss et al, 2008], induction of apoptosis in human skin melanoma HTB-140 cells [Jaszewska et al, 2009] and reduction of cell viability and cell invasiveness in human breast cancer MDA-MB-231 cells [Lewandowska et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present work was to assess the apoptotic and angiogenic activities of the procyanidin-rich EPFP towards non-invasive breast cancer cells (MCF-7) with respect to the expression of genes associated with these processes, and then to compare these results with those obtained for MDA-MB-231 cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…One report, from our laboratory, examines the effect of evening primrose flavanol preparation (EPFP), a flavanol preparation obtained from defatted seeds of evening primrose, on a highly invasive breast cancer cell line (MDA-MB-231) [15]. The aim of the present work was to assess the apoptotic and angiogenic activities of the procyanidin-rich EPFP towards non-invasive breast cancer cells (MCF-7) with respect to the expression of genes associated with these processes, and then to compare these results with those obtained for MDA-MB-231 cells [15].…”
Section: Introductionmentioning
confidence: 99%